The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004180000228
|View full text |Cite
|
Sign up to set email alerts
|

Localization of hepatocyte growth factor activator inhibitor type 1 in Langhans' cells of human placenta

Abstract: Activation of hepatocyte growth factor (HGF) is a crucial limiting step in HGF-induced signaling pathway. The HGF activator inhibitor type 1 (HAI-1) was identified as a potent inhibitor of HGF activator (HGFA), a serine proteinase that is responsible for the activation of HGF in vivo. HAI-1 is an integral membrane Kunitz-type serine proteinase inhibitor, and its mRNA has been reported to be most abundant in the placenta. In this report, specific antibody to HAI-1 was used in an immunohistochemical procedure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…In the placenta, where HAI-1 mRNA is most abundantly present, cytotrophoblasts and the epithelial cells of the amnionic membrane are strongly stained. 115 The immunohistochemical study also confirmed the injury-and regeneration-induced HAI-1 upregulation in the various epithelial tissues, such as the gastrointestinal mucosa, renal tissue and liver, 114 suggesting that HAI-1 is possibly involved in the survival and regeneration of the epithelial tissue. Various types of carcinoma cells also express HAI-1 immunohistochemically.…”
Section: Hai-1 Is An Epithelial Mt-kspi That Regulates Pericellular Amentioning
confidence: 99%
“…In the placenta, where HAI-1 mRNA is most abundantly present, cytotrophoblasts and the epithelial cells of the amnionic membrane are strongly stained. 115 The immunohistochemical study also confirmed the injury-and regeneration-induced HAI-1 upregulation in the various epithelial tissues, such as the gastrointestinal mucosa, renal tissue and liver, 114 suggesting that HAI-1 is possibly involved in the survival and regeneration of the epithelial tissue. Various types of carcinoma cells also express HAI-1 immunohistochemically.…”
Section: Hai-1 Is An Epithelial Mt-kspi That Regulates Pericellular Amentioning
confidence: 99%
“…Subsequent studies revealed that membrane‐associated serine proteases with trypsin‐like activity are primary targets of both HAIs . HAI‐1 is expressed by most epithelial cells and placental trophoblasts, and its most important cognate protease on the epithelial cell surface is matriptase, a type II transmembrane serine protease (TTSP). Other TTSPs such as hepsin, human airway trypsin‐like protease and TMPRSS13, as well as a glycosylphosphatidylinositol‐anchored serine protease prostasin, are also sensitive to HAI‐1 .…”
mentioning
confidence: 99%
“…At present we do not know the reason why HAI‐1 levels in the maternal plasma increased as pregnancy progressed. During pregnancy, HAI‐1 is produced mainly from placental villous cytotrophoblasts 19 . Morphological study showed that total number of cytotrophoblasts cells in the pregnant patients increased steadily until term 20 .…”
Section: Discussionmentioning
confidence: 99%